An Analysis of the Primary Energy Consumed by the Re-Liquefaction of Boil-off Gas of LNG Storage Tank. (August 2015) - Liu, Shengchun; Li, Xueqiang; Huo, Yan; Li, Hailin
Abstract: The pressure in liquefied natural gas (LNG) storage tank continues to increase due to the heat transfer from ambient air to low temperature LNG, which raises safety concerns. This research numerically analyzed the energy consumption of the re-liquefaction of BOG using the following four approaches: 1) a Claude cycle driven by electrical motor with the electricity produced by burning coal; 2) a Brayton cycle driven by a gas turbine fuelled by BOG released; 3) a Claude cycle driven by a SI engine fuelled by BOG; 4) using liquefied nitrogen produced in industry. With the efficiencies of the power system derived from industry data, the energy consumed of the re-liquefaction process was explored. The impact of heat transfer coefficient, LNG tank configuration, size, and percentage of LNG stored in tank on the rate of BOG and energy needed for the re-liquefaction of methane vapor were investigated. The primary energy ratio (PER), defined as the ratio of the energy recovered to the energy consumed, was examined and compared. The highest PER was observed using the Claude cycle driven by internal combustion engine fueled with BOG while the lowest PER was observed when BOG was cooled using liquefied nitrogen approach. The data presented in this paper provides the guideline for the management of pressure development in LNG storage tank and the design of accessory LNG storage system capable of re-liquefying the BOG gas to LNG.